THE TOWN AND THE SEA. PETROVSK AT THE CASPIAN SEA - Dalgat, El'mira Murtuzalievna (History, Archeology and Ethnography of the Caucasus, 2021)
The article attempts to demonstrate the transformation of the Russian military fortification Petrovskoe at the coast of the Caspian Sea into the large industrial center of the Dagestan region in the second half of the 19th – early 20th centuries, as well as to examine the role of the seaport in its economic development. Since 40s of the 19th century, the fort Petrovskoe was a transit point for cargo, transported by sea from Astrakhan for the Russian army, which was involved in war in Dagestan. The author considers the development of sea trade between Astrakhan, Baku and Petrovsk after the latter received the status of a city. The role of Petrovsk in the international trade in the Caspian Sea is shown. As new sources, we introduced data from the Statistical Committee of the Dagestan Region from the Central State Archives of the Republic of Dagestan, as well as materials from the collections of the State Historical Archives of the Republic of Azerbaijan. When writing the article, the author involved works of domestic and global historiography. The methodological basis of the article is the principle of historicism, which presupposes the study of any phenomenon in specific historical conditions and connections, as well as taking into account the decisive role of economic foundations for the development of society. The article reveals the development of Petrovsk and its seaport in the second half of the 19th – early 20th centuries, when Dagestan was integrated into the economic life of the Empire. Archival materials, published sources and historical literature were used when writing the paper. The author highlights that in the following third of the 19th century, sailing ships were replaced by steamships in the Caspian Sea. The place, occupied by the Petrovsky port among the ports of Russia in the Caspian is demonstrated. The article considers the goods brought to Petrovsk by sea and exported from it. The foundation of the textile factory “Caspian Manufactory” in Petrovsk in 1899 became possible thanks to the port. The construction of the Vladikavkaz railway intensified its role in the 90s of the 19th century. The author comes to the conclusion that the city of Petrovsk and its port played an important role in the process of integration of Dagestan into the economic space of the Russian Empire, and in the emergence of capitalist relations in the region.